Isolation and co-cultivation of human macrophages and neutrophils with Plasmodium falciparum-parasitized erythrocytes: An optimized system to study the phagocytic activity to malarial parasites. Issue 5 (October 2016) - Terkawi, Mohamad Alaa; Takano, Ryo; Kato, Kentaro
Abstract: Macrophages and neutrophils are our front line of defense against invading pathogens. They are professional phagocytic cells that play a key role in the clearance of Plasmodium falciparum -parasitized erythrocytes from the host circulation. A stable in vitro culture system for these cells and parasitized erythrocytes would provide the means to study their immunological responses to infection, potentially revealing important clues for new therapeutic interventions for malaria. Here, we present an optimized protocol for cultivating human peripheral blood monocyte-derived macrophages and neutrophils with Plasmodium falciparum -parasitized erythrocytes. Graphical abstract: Highlights: Isolation and cultivating macrophages and neutrophils. Phagocytic activity against iRBC. The protocol is beneficial for studying the immunological responses of phagocytes.